Palaeoenvironmental significance of middle Oxfordian deep marine deposits from La Manga Formation, Neuquén Basin, Argentina - Palma, R. M. (2014)
The Callovian-Oxfordian of the Neuquén Basin (Argentina) is characterized by an extensive marine carbonate system (La Manga Formation) with a predominance of shallow and middle ramp deposits, although locally in tectonically controlled settings, deeper deposits also formed. These middle Oxfordian deeper deposits consist of mudstone-wackestone carbonates alternating with black shales and show marked centimetre-scale rhythmicity, probably controlled by the Earth’s orbit parameters, mainly precession and eccentricity. The present study was designed to examine these deposits in terms of their sedimentology, geochemistry, and small-scale stratigraphy in Arroyo Los Blancos, southern Mendoza Province, where they are exceptionally well exposed and preserved. Results indicate that the sediments were deposited in an anoxic to dysoxic, relatively deep, sea-floor environment as revealed by the presence of: a) organic-rich shales, b) undisrupted lamination in most facies, c) pyrite framboids, and d) absence or scarcity of trace fossils and benthic fauna. Thin beds of graded wackestone-packstone and accumulations of thin shells of Bositra bivalves indicate sporadic reworking of the sea floor by weak currents. Organic petrology, Rock-Eval pyrolysis and thermal maturity indicators were used to characterize TOC and different types of organic matter. Low pyrolysis S yields along with low hydrogen indices suggest poor kerogen convertibility. Vitrinite reflectance (%Ro) ranged from 2.39 to 2.97 with an average of 2.70. The thermal alteration index (TAI) was 4+(5), indicating overmaturity. A tectono-sedimentary model is proposed for these deposits. According to this model, the relatively deep, organic-matter rich facies of La Manga Formation would have been deposited in the deepest zones of topographic lows controlled by tilting and differential subsidence of tectonic blocks bounded by normal faults.These faults were probably inherited from previous extensional tectonics of Late Triassic - Early Jurassic age.